Assessment of spatial and temporal changes in Histosol distribution in wetland areas in the Mosfell Valley - Tinganelli, Leone, 1964- (2013)
Since Iceland was settled by Scandinavian peoples around AD 874, intensive land-use and harsh climate of the Little Ice Age (ca. AD 1250/1500 to 1920) have led to significant degradation of vegetation and soil. This includes a removal of up to ~25000 km2 woodland from the lowlands. Theoretically, loss of woodland cover and lowered temperatures offer a situation in which an expansion of Histosol (highly organic, waterlogged soil) formation and other wetland could be expected. On the other hand, increased soil erosion has enhanced aeolian transportation and deposition of dust, which has changed irrevocably the structure of the Andic soils typical of Iceland. This study examines whether a change in the spatial dimensions Histosols in three wetland patches in Mosfellsdalur (Sveinamýri, Seljabrekka, and Stardalur) can be observed by extracting sediment profiles in transects through these areas. Bulk density (BD), soil organic matter (SOM) and soil moisture content (SMC) measurements were made to estimate their spatial distribution through the three wetland areas to reveal whether there has been change in the spatial coverage of Histosol from prehistoric periods, i.e. before landnám, to present days. Histosol have been found in some prehistoric sediment sections. However, significant changes in BD, SOM, and SMC values through the post-settlement sediment layers emphasize the transformation of these organic soils to mineral soils during history, whereas the spatial distribution of BD, SOM, and SMC values through the three catchments clearly indicate no post-settlement expansion of either Histosol or other wetland types. Frá landnámi Íslands, um 874 e. Kr, hefur áköf landnotkun og óhagstætt veðurfar litlu ísaldar (u.þ.b. 1250/1500 til 1920 e. Kr.) leitt til verulegrar hnignunar á jarðvegi og gróðri, meðal annars eyðingar á allt að 25000 km2 af skóglendi sem líklega óx á láglendi um tíma landnáms. Fræðilega séð, þá leiðir rýrnun skóglendis og lækkað hitastig til aðstæðna sem eykur myndun mójarðar (Histosol; mjög ...